The Influence of Human Resource Competency on the Performance of Service Employees Makassar City Tourism - Fitri Amalia; Edi Jusriadi; sitti nurbaya (CV. AFDIFAL MAJU BERKAH, 2024)
The purpose of this research is to determine the influence of human resource competency on the performance of Makassar City Tourism Department employees. The population of this study was 101 employees and the sample was 50 employees at the Makassar City Tourism Office. The sample data collection technique uses the Slovin formula. The type of data used is quantitative data. Data collection techniques were carried out using questionnaires, observation and documentation. In this research, the data sources used are primary data and secondary data. The instrument in this research uses the Likert scale method and statistical calculations using the Statistical for the Social Science (SPSS) version 26 application. Based on the research results, it shows that there is a positive and significant influence of Human Resource Competency on the Performance of Makassar City Tourism Office Employees. This was proven by a simple regression analysis test which obtained the results of the human resource competency t test with tcount = 3.091 > ttable = 2.010. In addition, it was found that the significant value of human resource competency on employee performance was 0.003 < 0.05. So it can be concluded that H1 is accepted.